AKTIVITAS ANTIBAKTERI SIRUP EKSTRAK KULIT BUAH SEMANGKA (Citrullus lanatus Thunb.) TERHADAP Escherichia coli - Ermawati Ermawati (Jurnal Kesehatan Yamasi Makassar, 2022)
This study aims to find out the activity of watermelon skin extract syrup (Citrullus lanatus Thunb) against Esherichia coli. Watermelon peel extract is made in syrup preparations with concentrations of 5%, 10%, and 15%. Antibacterial activity testing of Esherichia coli was tested using the disc diffusion method. Then observations are made by measuring the bland zone that occurs in each formula in the test bacteria and produces a strong category of bland zones because the activity of the bland zone ranges (>10-20 mm). Statistical results were not significant between negative controls and all formulas, whereas not significant were seen between all formulas. The conclusion obtained is that watermelon peel extract can inhibit the growth of Eschericia coli.